Role of allopregnanolone on cerebellar granule cells neurogenesis - Keller, Elizabeth Ana (2004)
The role of allopregnanolone on immature cerebellar granule cells (CGC) proliferation was studied. Allopregnanolone (0.1–1 μM) increased [3H]thymidine incorporation and cell number determined by neuronal counting and by an MTT colorimetric assay. The effect of the neurosteroid was completely prevented by preincubation with 10 mM MgCl2, 10 μM nifedipine, 10 μM picrotoxin or by 50 μM bicuculine. We conclude that ALLO affects cerebellar neurogenesis by increasing calcium influx through voltage-gated calcium channels and GABAA receptors activation.